2005
DOI: 10.1210/jc.2004-0241
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Presence of Toll-Like Receptor 4 System in the Human Endometrium

Abstract: We investigated whether Toll-like receptor (TLR) 4 is at work in the human endometrium. The expression of TLR4 mRNA in endometrial epithelial cells (EECs) and stromal cells (ESCs) was detected by RT-PCR and in situ hybridization. Western blotting analysis revealed the TLR4 protein expression in both cell populations. Treatment of lipopolysaccharide (LPS), the actions of which are mediated through TLR4, significantly increased IL-8 secretion from cultured ESCs in a dose-dependent fashion. The stimulatory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 35 publications
(25 reference statements)
4
111
0
1
Order By: Relevance
“…Endometrial, cervical and Fallopian tube epithelial cells have both been shown to respond to the TLR3 ligand, poly I:C, with increased cytokine output (Lesmeister et al 2005, Andersen et al 2006, Ghosh et al 2008, Nasu et al 2007. Fallopian tube fibroblasts and endometrial epithelial and stromal cells have been shown to increase inflammatory mediator output in response to LPS (lipopolysaccharide), a TLR4 ligand (Hirata et al 2005, Itoh et al 2006. These in vitro data suggest that TLRs on reproductive tract cells will be capable of responding to pathogen products in vivo.…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 99%
“…Endometrial, cervical and Fallopian tube epithelial cells have both been shown to respond to the TLR3 ligand, poly I:C, with increased cytokine output (Lesmeister et al 2005, Andersen et al 2006, Ghosh et al 2008, Nasu et al 2007. Fallopian tube fibroblasts and endometrial epithelial and stromal cells have been shown to increase inflammatory mediator output in response to LPS (lipopolysaccharide), a TLR4 ligand (Hirata et al 2005, Itoh et al 2006. These in vitro data suggest that TLRs on reproductive tract cells will be capable of responding to pathogen products in vivo.…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 99%
“…Isolation and culture of human EEC and ESC was as described previously (21)(22)(23)(24). Endometrial tissues were minced and incubated in DMEM/F12 containing 0.25% type I collagenase and 15 U/ml DNase I for 60 min at 37°C.…”
Section: Isolation Purification and Culture Of Endometrial Epithelimentioning
confidence: 99%
“…Flow cytometric analysis was performed as we have reported previously (22). Adherent cells (EEC, ESC, and trophoblast cells) were detached by using 0.25% trypsin/EDTA.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…The endometrium provides a barrier against infection and an opportunity to detect bacteria by innate immune receptors recognising PAMPs (Beutler, 2004). In the human endometrium, nine TLRs are expressed at the mRNA level including TLR4 (Pioli et al, 2004;Young et al, 2004;Hirata et al, 2005;Schaefer et al, 2005). It is the role of TLR4 to detect LPS, although signalling through TLR4 also requires accessory molecules such as CD14, LBP and MD2 (Beutler, 2003 and2004).…”
Section: Cellular Mechanismsmentioning
confidence: 99%